2011
DOI: 10.1111/j.1708-8208.2009.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Systemic Bone Mineral Density and Local Bone Quality as Effectors of Dental Implant Survival

Abstract: Systemic BMD and osteoporotic status are not associated with local jawbone quality. Implants placed in good-quality bone, as assessed subjectively by the surgeon at the time of implant placement, have significantly better survival characteristics than implants placed in moderate-/poor-quality bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 7 publications
3
30
1
2
Order By: Relevance
“…Three other studies [15-17] did not find any significant differences for implantation success neither for osseointegration quality between osteoporotic and control groups. Holahan et al [16] found that osteoporosis did not show any correlation to local jaw bone quality, but when it was, set subjectively by surgeon, it highly correlated with implantation success (P < 0.01). It should be noted that Mozzati et al [15] combined many different implantation methods, such as immediate function loading, immediate implantation and sinus lifting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three other studies [15-17] did not find any significant differences for implantation success neither for osseointegration quality between osteoporotic and control groups. Holahan et al [16] found that osteoporosis did not show any correlation to local jaw bone quality, but when it was, set subjectively by surgeon, it highly correlated with implantation success (P < 0.01). It should be noted that Mozzati et al [15] combined many different implantation methods, such as immediate function loading, immediate implantation and sinus lifting.…”
Section: Resultsmentioning
confidence: 99%
“…There are several different osteoporosis aetiology theories, asserting the lack of oestrogen, calcium circulation disorders, thyroid dysfunction as main causing factor [55,57,58]. Due to the demonstrated effect of oestrogen insufficiency, in many studies only post-menopausal females were included [15,16,19,24,26]. However, in none of the studies laboratorial hormonal examinations were performed, only stating that post-menopausal women are in higher risk for osteoporosis without individual examinations.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the poor bone quality in which some of the implants were placed. Some authors suggest that lower quality of bone is associated with a higher failure rate [31] which is true in areas like the posterior maxilla or augmented bone [32,33] so it would be expectable that the results of this SR presented higher failure rates when comparing to standard implants placed in native bone. However, two recently published meta-analysis reported annual failure rates between 2 and 3% [34,35] that are well within the values obtained in this systematic review for short implants and standard implants in augmented bone.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Interest in the impact of local factors on implant survival has additionally been the focus of many reports that identify bone quality and quantity, as well as implant stability data. [7][8][9] However, given such a low incidence of device failure, it can be appreciated that large numbers of implants should be followed for long periods of time to best discern meaningful associations.…”
Section: Commentary and Analysismentioning
confidence: 99%